Immunogenicity and safety of a second administration of 13-valent pneumococcal conjugate vaccine 5 years after initial vaccination in adults 50 years and older. Issue 30 (24th June 2016) - Frenck, Robert W.; Fiquet, Anne; Gurtman, Alejandra; van Cleeff, Martin; Davis, Matthew; Rubino, John; Smith, William; Sundaraiyer, Vani; Sidhu, Mohinder; Emini, Emilio A.; Gruber, William C.; Scott, Daniel A.; et al.
Highlights: Adults ≥50 years, were revaccinated with PCV13 five years after initial vaccination. Immune responses significantly increased from before to 1 month after revaccination. Immune responses were maintained or enhanced for most vaccine serotypes by revaccination. The safety profile after PCV13 revaccination was acceptable. Abstract: Background: Vaccination effectively reduces invasive disease and pneumonia caused by Streptococcus pneumoniae . However, waning antibody titers and the ability of revaccination to boost titers in older adults have been concerns. A study to describe antibody persistence after vaccination with 13-valent pneumococcal conjugate vaccine (PCV13) and response to revaccination 5 years after the initial dose was conducted. Methods: Pneumococcal vaccine–naive subjects aged 50–59 years were randomized and vaccinated with PCV13 plus trivalent inactivated influenza vaccine concomitantly or 1 month apart, then revaccinated with PCV13 five years later. Antipneumococcal polysaccharide opsonophagocytic activity (OPA) geometric mean titers (GMTs) and immunoglobulin G (IgG) geometric mean concentrations (GMCs) were determined before and approximately 1 month after each vaccination. Targeted local reactions and systemic events were collected for 14 days, adverse events (AEs) for 1 month, and serious AEs (SAEs) for 6 months after each vaccination. Results: Of 1116 randomized subjects, 727 were revaccinated at year 5. Between the time of initial vaccination and revaccination, OPA GMTs and IgG GMCs declined but remained higher than levels before initial vaccination for 12 of the 13 vaccine serotypes. One month after revaccination, OPA GMTs and IgG GMCs were comparable with, or higher than, levels observed 1 month after initial vaccination for most vaccine serotypes. Local reactions were mostly mild. AEs were reported by <5% and SAEs by <1% of subjects at 1 and 6 months after revaccination, respectively. No SAEs were vaccine-related. Conclusions: Revaccination of adults ≥50 years with PCV13 five years after primary vaccination was safe and immunogenic. Additionally, antibody titers were maintained for at least 5 years after vaccination. The vaccine stimulated a memory response as shown by enhanced responses that were maintained or enhanced by revaccination. ClinicalTrials.gov registration: NCT00521586.